HUBUNGAN ANTARA PENYESUAIAN DIRI DENGAN PROKRASTINASI AKADEMIK SISWA SEKOLAH BERASRAMA SMP N 3 PETERONGAN JOMBANG - Zakiyah, Naili; Nuzulia, Frieda; Setyawan, Imam (Faculty of Psychology, Diponegoro University, 2010)
An education alternative proposed to generate well qualified human resources is boarding type school which is located in Islamic boarding school. Boarding school students are faced with very different situation than home. Dense activities make the students should be capable of dividing time for school, boarding house and other activities. Overcapacity in the boarding house makes it possible to evoke low supervision situation. That condition enables students susceptible with procrastinate behavior, particularly in academic field. Academic procrastination is a habit which can causes various negative consequences, like time wasting and school tasks abandoning.This research is purposed to study the relation of self-adjustment with academic procrastination to the students of SMP N 3 Jombang. This research used cluster random sampling technique. Researched subjects were 97 students. Researched measuring instrument used self-adjustment scale with 26 items (Î± = 0,877) and academic procrastination scale with 27 items (Î± = 0,898). Both scales are arranged with Likert mode scaling and its analysis statistic is used computer program SPSS version 16.0. Simple regression analysis resulted rxy = -0.463, with p = 0,000 (p<0,05).The result shows that there is a negative relation between self-adjustment with academic procrastination. The higher the student self adjustment, the lower the academic procrastination. Determination coefficient is 0,214, means that self adjustment gives effective contribution of 21,4% to academic procrastination. The remainder of 78,6% is determined by other factors which are not revealed in this research.Keywords: Self-Adjustment, Academic Procrastination, Boarding SchoolPermalink :